"Sa raket kumakapit, sa raket din sumasabit" the working conditions of Filipino photojournalists in Metro Manila under the GIG economy - Morales, Bernadette Anne M.
This study, based on interviews and focus groups with Filipino photojournalists, examines their motivations, labor struggles, and aspirations within the neoliberal gig economy. Findings reveal that photojournalists earn less than their monthly expenses from photojournalism alone, compelling them to join the gig economy out of economic necessity rather than choice. This contradicts the widely promoted image of the gig economy as empowering and beneficial. Despite systemic exploitation—marked by low pay, job insecurity, and lack of social protections—Filipino photojournalists remain committed to public service and actively organize for labor rights, identifying with the broader working class. The study recommends improving working conditions through standardized pay rates, expanded legal protections, and social benefits such as insurance and hazard pay. It also calls for labor law reforms to recognize the unique status of gig workers, promotion of unionization, and collective bargaining to ensure workplace equity and accountability. Taxation and labor classifications should be updated to reflect the complexities of freelancing, reducing dependence on precarious gig work. Using labor process theory, the research highlights the contradictions between capital and labor, emphasizing the urgent need for both structural reforms and systemic change to achieve labor justice in photojournalism.